High frequency automatic recording package data summary report PS05, August 4, 2008 -- January 6, 2009 - Margolina, Tetyana (Monterey, California. Naval Postgraduate School, 2010)
This is the first in a series of reports on the project, which seeks to assemble a census of marine mammal vocalizations in the high-frequency acoustic recording package (HARP, Wiggins and Hildebrand, 2007) data collected by the NPS Oceanography Department off Point Sur beginning in October 2006. The present report provides an initial summary of marine mammal vocalizations detected and identified in records from the fifth HARP deployment between August 4, 2008 and January 6, 2009. Data was acquired in the 10 Hz--100 kHz frequency band at a 200 kHz sampling frequency for 5 minutes during each quarter hour. Long-term spectral averages were created for three frequency bands (10 Hz- 1000 Hz, 1 kHz-5 kHz, 5 kHz-100 kHz) and then scanned for marine mammal vocalizations. Detected calls of blue whales, fin whales, humpback whales, as well as echolocations of sperm whales, beaked whales, and dolphins are presented as occurrence time diagrams. N00244-10-1-0031.